DOptik : Index Card Match Learning Application to Improve Students’s Learning Outcomes in Light Diffraction (Feasibility Test) - Jalil, Asimi Rafsan; Puri, Putri Rose Amanda; Setiaji, Bayu (Universitas Negeri Padang, 2023)
The success of a learning is influenced by several factors. Media and learning models are important factors in supporting learning success. This study aims to develop physics learning applications, especially in light diffraction materials that are suitable for use by high school students based on active learning type Index Card Match (ICM) to improve student learning outcomes especially in the post-covid-19 pandemic era. By using learning media in the form of applications and active learning models, learning can take place effectively and conducively so that student learning outcomes can increase. The method used is a 4D model, but only up to the development stage. The feasibility of this blueprint application was tested using a questionnaire that has 10 questions with 6 indicators and involves 24 students from several universities in Indonesia who are studying physics. The results of the questionnaire were analyzed using the interval success method and then categorized into 4 Assessment Scales. The results showed that the learning application developed is very feasible to use on all indicators that got 4.095 on average final score. This blueprint application can be developed into applications that are ready for use by students and applications that can be developed at the material and other levels. The results showed that the learning application developed is very feasible to use on all indicators that got 4.095 on average final score. This blueprint application can be developed into applications that are ready for use by students and applications that can be developed at the material and other levels. The results showed that the learning application developed is very feasible to use on all indicators that got 4.095 on average final score. This blueprint application can be developed into applications that are ready for use by students and applications that can be developed at the material and other levels.